PhD : The Pursuit of Excellence - Kamarul Zaman Ahmad, author 270814; Gale Group (Online service) 651863 (Singapore : Cengage Learning Asia, 2007)
Aims to assist a final year Master's student or graduate in making an informed decision on whether or not to pursue a PhD. Provides the reader with an understanding of what a PhD actually is and what it can do for the holder. Explains the structure of the thesis, the process of gathering information and writing.